PENGGUNAAN EJAAN PADA SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN SEJARAH UNIVERSITAS LAMPUNG TAHUN 2012 - Valentia Pratiwi; ni nyoman wetty; siti samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Main problem which occured in this reaserch is using spelling for the students’ thesis of Lampung University in teacher training and education faculty of history education study program in 2012 and successfully to be conducted. The purpose of  reasearch is to describe about what is right and error in using spelling for the students’ thesis of Lampung University in teacher training and education faculty of history education study program in 2012. The reasercher used qualitative describing method in collecting the data. The sources in this reaserch is the students’ thesis of teacher training and education faculty of history study program for March period in 2012, and amounted about nine papers. Data was gained by documentary technique which held by the researcher in several weeks. In analyzing, data went to the theories of Miles and Huberman which stated by three steps are (1) reduction, (2) application, and (3) conclusion or verification. The result of this research told about 5.890 people or 93% was right in using spelling for their thesis and 429 others or 7% was still error in the written of theirs. In using spelling, it must be constructed by capital and italic letters, derivation words, suffix –di, numbering and count, using full-stop, and comma.Key Words: spelling, using the letter, writing the word, and panctuation.